The International Experience in Addressing the Socio-Economic Issues of Forcibly Displaced Persons and its Localization in Armenia - Hakobjanyan, Anna; Mirzoyan, Narine; Hayrapetyan, Davit («ԱՐՑԱԽ» հրատ.)
This article analyzes global practices in addressing the socio-economic challenges of forcibly displaced persons and explores how these can be localized in Armenia, with a specific focus on forcibly displaced students from Artsakh. It aims to identify key integration barriers faced by these students in higher education, including socio-economic hardships, legal and citizenship issues, and psychological well-being. A resource-based model for integration was developed, and field surveys involving over 200 Artsakh students were conducted. Quantitative and qualitative analyses revealed three main categories of challenges: socio-economic issues (e.g., lack of housing, employment difficulties), social and interpersonal barriers (e.g., negative societal attitudes toward displaced persons), and individual psychological struggles (e.g., uncertainty about the future). Հոդվածում վերլուծվում է հարկադիր տեղահանված անձանց սոցիալ-տնտեսական խնդիրների լուծման համաշխարհային փորձը և ուսումնասիրում, թե ինչպես կարելի է տեղայնացնել այդ մոտեցումները Հայաստանում՝ հատուկ ուշադրություն դարձնելով Արցախից բռնի տեղահանված ուսանողներին։ Հոդվածի նպատակն է բացահայտել բուհական համակարգում նրանց ինտեգրման հիմնական խոչընդոտները, այդ թվում՝ սոցիալ-տնտեսական դժվարությունները, իրավական ու քաղաքացիության հետ կապված հարցերը և հոգեբանական բարեկեցությունը։ В статье анализируется мировой опыт решения социально-экономических проблем вынужденно перемещённых лиц и исследуются возможности локализации этих практик в Армении, акцентируя особое внимание на состоянии вынужденно перемещённых студентов из Арцаха.
Keywords: Տնտեսագիտություն